Structuralvariations in thespike glycoproteinof M41 and CR88 (4/91) avian infectious bronchitis viruses - Bande, Faruku; Arshad, Siti Suri (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2015)
Infectious bronchitis virus (IBV) caused economically important poultry disease worldwide. In this study, bioinformatics tools were used to determine the structural properties and phylogenetic relationship of the spike (S1) glycoproteins of M41 and CR88-IBV strains. Structural analyses revealed that M41 and CR88 IBV strains vary in terms of their primary and secondary structures, the phylogenetic relationship and N-glycosylation sites. Multiple sequence alignment revealed 93.1% and 98.4% nucleotide pairwise sequence similarities among CR88 and M41 IBV strains respectively. Both CR88 and M41 isolates phylogenetically clustered into different subgroups, including the pathogenic and vaccine strains. There were eight conserved N-glycosylation sites in the form of ASN-XAA-SER/THR occurring in different locations in the S1-gene of CR88 and six sites in M41 isolates. These variations and their possible implications were discussed.